„Die schlimmste Seuche unserer Tage ist die Angst.“ – Krankheit und Pandemie in Thea Dorns Trost. Briefe an Max - Uysal Ünalan, Saniye (Moderna Språk, 2024)
In the course of the pandemic since 2020 we have experienced different ways of life in public and private spaces, healthcare as well as work. Doris Bachmann-Medick talks about a ‘pandemic turn’ and claims, that the coronavirus pandemic implies a kind of crisis situation for human existence in our global reality. Everything has changed with the pandemic. Especially the biopolitical measures as well as health policy have entailed significant changes in social and individual living conditions. Literary discourses as a particular part of culture have the significant potential to reflect and criticize certain aspects of society and culture. Thea Dorn’s Corona novel Trost. Briefe an Max can obviously be described as a reaction to and literary reception of the Corona-era since 2020. The first-person narrator Johanna works as a culture journalist. She recently lost her mother, who travelled to Italy despite the pandemic. In her letters to her philosophy teacher, she expresses her immeasurable sadness and anger due to the new way of living because of the pandemic. The critical attitude of the novel is remarkable in terms of absolutization since helping becomes a part of biopolitics in times of the pandemic that leads to a tragic situation for the subject. In this article, I will analyze Thea Dorn’s Trost. Briefe an Max with reference to the approaches of Giorgio Agamben in Homo Sacer concerning biopolitics. In this context, especially the critical potential and attitude of this novel get important.